2013
DOI: 10.1371/journal.pone.0075923
|View full text |Cite
|
Sign up to set email alerts
|

A Single Hot Event That Does Not Affect Survival but Decreases Reproduction in the Diamondback Moth, Plutella xylostella

Abstract: Extremely hot events (usually involving a few hours at extreme high temperatures in summer) are expected to increase in frequency in temperate regions under global warming. The impact of these events is generally overlooked in insect population prediction, since they are unlikely to cause widespread mortality, however reproduction may be affected by them. In this study, we examined such stress effects in the diamondback moth, Plutella xylostella. We simulated a single extreme hot day (maximum of 40°C lasting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 52 publications
3
69
0
1
Order By: Relevance
“…the proportion and total number of eggs laid per day. Consistent with previous studies, we found that high temperatures generally led to a reduction in maximum egg production at the start of the oviposition period (Krebs and Loeschcke 1994;Janowitz and Fischer 2011;Zhang et al 2013). However, we also found that high temperatures led on average, to a faster decline in egg production with age (Fig.…”
Section: Stage-specific Heat Effects and Adult Reproductive Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…the proportion and total number of eggs laid per day. Consistent with previous studies, we found that high temperatures generally led to a reduction in maximum egg production at the start of the oviposition period (Krebs and Loeschcke 1994;Janowitz and Fischer 2011;Zhang et al 2013). However, we also found that high temperatures led on average, to a faster decline in egg production with age (Fig.…”
Section: Stage-specific Heat Effects and Adult Reproductive Performancesupporting
confidence: 92%
“…62N, 114.13E) in Wuhan, China. The captive population was reared on an artificial diet at 25 ± 1 °C, 30-40 % relative humidity (RH) and a photoperiod of 15:9 h (light:dark), as described by Zhang et al (2013).…”
Section: Stock Rearingmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that T max will reduce fitness to 0 when it reaches a critical threshold. During the daytime, episodic high temperatures can lead to a series of severe physiological and developmental problems in organisms (Denlinger and Yocum, 1998;Karl et al, 2011;Zhang et al, 2013) and further result in mass mortality (Welbergen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While average temperatures in temperate regions are rarely expected to exceed optimum temperatures for many organisms (Deutsch et al, 2008), T max on summer days is often predicted to surpass critical thermal maxima (Kearney et al, 2009;Bale and Hayward, 2010), resulting in stressful conditions for many midlatitude ectotherms Zhang et al, 2013;Vasseur et al, 2014). Even small increases in maximum temperature may impact organism phenology (Semenov, 2009), species distribution (Overgaard et al, 2014), population dynamics (Welbergen et al, 2008) and community structure (Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%